Evaluation of the Drug–Drug Interaction Potential of the GlyT1 Inhibitor Iclepertin (BI 425809): A Physiologically Based Pharmacokinetic (PBPK) Modeling Approach - Elin M. Matsson; Michael Desch; Valerie Nock; Nina Hanke (CPT: Pharmacometrics & Systems Pharmacology)
ABSTRACT Despite predicting poor functional outcomes and being a significant patient burden, there are no approved pharmacotherapies to treat symptoms of cognitive impairment associated with schizophrenia (CIAS). Iclepertin (BI 425809) is a potent and selective inhibitor of glycine transporter‐1 (GlyT1) that was in Phase III development for the treatment of CIAS. Iclepertin is metabolized by the cytochrome P450 (CYP) 3A4 enzyme and also induces CYP3A4 at supratherapeutic concentrations, so drug–drug interactions (DDIs) with CYP3A4 perpetrators and substrates may be expected. A physiologically based pharmacokinetic (PBPK) model was built and qualified based on physiochemical, in vitro, and Phase I clinical data of iclepertin that included different administration routes, formulations, dose levels, single‐ and multiple‐dose administrations and food statuses. The iclepertin PBPK model was further qualified using clinical data of DDIs with a strong CYP3A4 inducer (rifampicin) and a strong CYP3A4 inhibitor (itraconazole). The qualified model was then applied to simulate DDIs of iclepertin 10 mg daily (the intended therapeutic dose) as a victim or perpetrator drug of CYP3A4. Based on the thorough qualification with clinical DDI data, the model was deemed qualified to predict new, untested clinical scenarios such as alternative drug doses, coadministration of different CYP3A4 substrates, coadministration of weak–moderate inducers and inhibitors of CYP3A4, and in the setting of polymedication in vivo. The model allows detailed analyses of DDI behaviors to inform appropriate prescribing of concomitant medications in patients treated with iclepertin.